Hypoxia-inducible factor 1-alpha is a driving mechanism linking chronic obstructive pulmonary disease to lung cancer - Xu, Yuan-rui; Wang, An-long; Li, Ya-qing (Frontiers in Oncology, 2022)
Patients with chronic obstructive pulmonary disease (COPD), irrespective of their smoking history, are more likely to develop lung cancer than the general population. This is mainly because COPD is characterized by chronic persistent inflammation and hypoxia, which are the risk factors for lung cancer. However, the mechanisms underlying this observation are still unknown. Hypoxia-inducible factor 1-alpha (HIF-1α) plays an important role in the crosstalk that exists between inflammation and hypoxia. Furthermore, HIF-1α is the main regulator of somatic adaptation to hypoxia and is highly expressed in hypoxic environments. In this review, we discuss the molecular aspects of the crosstalk between hypoxia and inflammation, showing that HIF-1α is an important signaling pathway that drives COPD progression to lung cancer. Here, we also provide an overview of HIF-1α and its principal regulatory mechanisms, briefly describe HIF-1α-targeted therapy in lung cancer, and summarize substances that may be used to target HIF-1α at the level of COPD-induced inflammation.